2015
DOI: 10.1016/j.jebo.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Attention, intentions, and follow-through in preventive health behavior: Field experimental evidence on flu vaccination

Abstract: a b s t r a c tPreventive health behaviors like flu vaccination have important benefits, but compliance is poor, and the reasons are not fully understood. We conducted a large study across six colleges (N = 9358), with a methodology that offers an unusual opportunity to look at three potential factors: inattention to information, informed intentions to not comply, and problems following through on intentions. We also tested three interventions in an RCT. We find that inattention to information is not the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 48 publications
2
75
1
Order By: Relevance
“…As for price-based policies, Bronchetti, Huffman, and Magenheim (2015) found that offering a $30 incentive ($31.07 in 2015 dollars) increased vaccination rates at campus clinics by 10.7 percentage points. The baseline vaccination rate in the control group was 8.7%, so the treatment generated just 1.78 additional vaccinations per $100 spent (0.107/(31.07 × (0.107 + 0.087)) × 100).…”
Section: Resultsmentioning
confidence: 99%
“…As for price-based policies, Bronchetti, Huffman, and Magenheim (2015) found that offering a $30 incentive ($31.07 in 2015 dollars) increased vaccination rates at campus clinics by 10.7 percentage points. The baseline vaccination rate in the control group was 8.7%, so the treatment generated just 1.78 additional vaccinations per $100 spent (0.107/(31.07 × (0.107 + 0.087)) × 100).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this is a cross-sectional study, with all of its inherent limitations. In addition, future studies are needed to clarify whether there is an intention-action gap [53, 54] in the association between psychological factors and flu vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Active-Decision Nudge (Carroll et al, 2009) Danish Tax Incentives (Chetty et al, 2014) Retirement Savings Information (Duflo & Saez, 2003) Matching Contributions: 20% (Duflo et al, 2006) Matching Contributions: 50% (Duflo et al, 2006) U.S. Tax Incentives (Duflo et al, 2007) Form-Streamlining Nudge (Bettinger et al, 2012) Monthly Stipends (Dynarski, 2003) Monetary Subsidies (Long, 2004a) Tax Credits (Long, 2004b;Bulman & Hoxby, 2015) Social-Norms Nudge (Allcott, 2011) Health-Linked Usage Information Nudge (Asensio & Delmas, 2015) Billing-Information Nudge (Asensio & Delmas, 2015) Electricity Bill Discounts (Ito, 2015) Incentives and Education (Arimura et al, 2012) Planning-Prompt Nudge (Milkman et al, 2011) Default-Appointment Nudge (Chapman et al, 2010) Monetary Incentive (Bronchetti et al, 2015) Educational Campaign (Kimura et al, 2007) Free Work-Site Vaccinations (Kimura et al, 2007) return the form was approximately $2 per employee, so the active-decision nudge generated $100 of additional savings per dollar spent. Perhaps the best-known nudges for promoting savings in workplace retirement accounts enroll employees automatically, use automatic escalation to increase their contribution rates, or employ a combination of these two nudges.…”
Section: Nudgementioning
confidence: 99%